Classification Differences in Food Insecurity Measures between the United States and Canada: Practical Implications for Trend Monitoring and Health Research. Issue 4 (30th December 2021) - Men, Fei; Tarasuk, Valerie
ABSTRACT: Background: Food insecurity, inadequate access to food due to financial constraints, is a major public health issue in the United States and Canada, where the same 18-item questionnaire is used to monitor food insecurity. Researchers often assume that findings on food insecurity from the 2 countries are comparable with each other, but there are between-country differences in how food insecurity status is determined. Objectives: We aimed to compare the distribution of household food insecurity in the Canadian population applying the US and Canadian classification schemes. We also examined the extent to which associations between food insecurity and adults' health differ under the 2 schemes. Methods: We used the population-representative Canadian Community Health Survey 2005–2017 linked to administrative health records. Food insecurity was measured by the Household Food Security Survey Module. Adults 18 y and older with valid food insecurity status were included from all jurisdictions except Quebec ( n  = 403, 200). We cross-tabulated food insecurity status classified by the US and Canadian schemes. We also fitted logistic regressions on self-reported and objective health measures adjusting for confounders. Results: Applying the Canadian classification scheme, 7.7% of households were food insecure; the number fell to 6.0% with the US scheme. Associations between food insecurity status and health measures were mostly similar across classification schemes, although the associations between food insecurity and self-reported health were slightly larger if the US scheme was applied. Marginal food security/insecurity was associated with worse health measures irrespective of the classification scheme. United States–Canada discordance in classification of marginal food security/insecurity had a limited effect on health prediction. Conclusions: United States–Canada differences in classification affected the apparent distribution of household food insecurity but not the associations between food insecurity and measures of adult health. Marginal food security/insecurity should be set apart from the food-secure group for trend monitoring and health research.